PELATIHAN PEMBUATAN APLIKASI PEMBELAJARAN BERBASIS ANDROID BAGI GURU IPA SMP DI KABUPATEN LAMPUNG SELATAN - Berti Yolida; Median Agus Priadi; Rini Rita T. Marpaung; Novinta Nurulsari (Ruang Pengabdian : Jurnal Pengabdian Kepada Masyarakat, 2022)
The objectives of this community service activity are: 1) increasing teacher knowledge regarding open-source biology applications based on Android, which can be used as learning media in the new normal era; and 2) improving teacher skills in using open-source biology applications based on Android as learning media in the new normal era. This community service activity targets science teachers who are members of the Science MGMP of South Lampung Regency. Community service activities were carried out at SMP Negeri 3 Natar, South Lampung. This service activity adopts a training model with methods of providing material, discussion and feedback, group practice, and independent activities accompanied by mentoring. This service activity will be evaluated for the implementation and sustainability of the program using the CIPP evaluation model. Service activities were declared successful if the average ability of junior high school science teachers increased by ≥ 80%. Based on the results of the activities, it was concluded that these training activities effectively increased teachers' abilities in making learning media based on Android applications. This is based on increasing teachers' understanding of the design of android application-based learning media for junior high school science teachers in the South Lampung Regency. Based on the results of the initial evaluation, it was found that the teachers' initial understanding was low. At the end of the training, the teacher's understanding and ability to utilize and create teacher learning media were higher than before attending the training. As many as 80% of teachers can make learning media based on Android applications. An improved understanding of teachers designing learning media based on Android applications is classified as good. ABSTRAKTujuan kegiatan pengabdian ini adalah: 1) meningkatkan pengetahuan guru terkait aplikasi open-source biologi berbasis android yang dapat digunakan sebagai media pembelajaran di era new normal; dan 2) meningkatkan keterampilan guru dalam menggunakan aplikasi open-source biologi berbasis android sebagai media pembelajaran di era new normal. Sasaran kegiatan pengabdian ini adalah guru-guru IPA yang tergabung dalam MGMP IPA Kabupaten Lampung Selatan. Kegiatan pengabdian dilaksanakan di SMP Negeri 3 Natar Lampung Selatan. Kegiatan pengabdian ini mengadopsi model pelatihan dengan metode pemberian materi, diskusi dan umpan balik, praktik berkelompok, dan kegiatan mandiri disertai pendampingan. Kegiatan pengabdian ini akan dievaluasi pelaksanaan dan keberlanjutan program menggunakan model evaluasi CIPP. Kegiatan pengabdian dinyatakan berhasil apabila rerata kemampuan guru-guru IPA SMP mengalami peningkatan sebesar ≥ 80% .Berdasarkan hasil kegiatan, diperoleh simpulan bahwa kegiatan pelatihan ini efektif dalam meningkatkan kemampuan guru dalam pembuatan media pembelajaran berbasis aplikasi android. Hal ini didasarkan pada peningkatan pemahaman guru- guru tentang perancangan pembuatan media pembelajaran berbasis aplikasi android bagi guru-guru IPA SMP di Kabupaten Lampung Selatan. Berdasarkan hasil evaluasi awal diketahui bahwa pemahaman awal guru-guru tergolong rendah. Pada akhir pelatihan, pemahaman dan kemampuan guru dalam memanfaatkan dan membuat media pembelajaran guru-guru lebih tinggi dibandingkan dengan sebelum mengikuti pelatihan. Sebanyak 80% guru mampu membuat media pembelajaran berbasis aplikasi android. Peningkatan pemahaman guru-guru perancangan pembuatan media pembelajaran berbasis aplikasi android tergolong Baik.  DOI: https://doi.org/10.23960/rp/v2i2.hal.112-122